Distal femur fractures in the elderly population treated with fibular allograft and lateral plating only: the surgical technique - Vanessa Morello, MD; Gregory Berry, MDCM, MSEd, FRCSC; Mitchell Bernstein, MD, FRCSC; Alexandra Bunting, MD; Edward Harvey, HBSc, MSc, MDCM, FRCSC; Rudolf Reindl, MD, FRCSC (OTA International)
Abstract. Distal femoral fractures are increasingly observed in the elderly population, often presenting with osteoporotic bone characteristics. Surgical fixation remains the gold standard, with lateral locking plates being the most commonly used method. To prevent hardware failure and varus collapse in osteoporotic bone, various surgical techniques and augmentation strategies have been proposed. We describe a surgical technique for managing osteoporotic, comminuted distal femur fractures using a fibular strut allograft in combination with a lateral-only locking plate, along with outcomes in patients treated with this approach. When an intra-articular component was present, it was addressed first. Through the zone of comminution and a cortical window created in the lateral condyle, a fibular strut allograft was inserted into the femoral canal extending into the epiphysis. Once satisfactory alignment and reduction were confirmed radiographically, a lateral locking plate was applied, bridging any existing proximal implants. Proximal screws were inserted percutaneously, while multiple screws were directed through the fibular graft for enhanced stability. The combination of a fibular strut allograft with a lateral locking plate offers a reliable option for treating comminuted distal femur fractures with osteoporotic features, minimizing displacement and reducing the risk of implant failure without necessitating additional medial support or secondary implants.